Double-sided dotted adhesive tape and preparation method thereof

By using dot-shaped structure of double-sided dot tape and high-molecular-weight acrylate copolymer adhesive, the problem that traditional tape cannot effectively dissipate heat is solved, efficient bonding and heat dissipation of electronic components is achieved, and the service life of electronic products is extended.

CN119799180APending Publication Date: 2025-04-11CROWN TAICANG ADHESIVE PROD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411998844.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Due to the planar structure of traditional double-sided tape, the heat from electronic components cannot be discharged in time, resulting in heat generation of electronic products and affecting the performance and life of the electronic products.

Method used

Double-sided dot tape is used, and its dot structure is designed to form an exhaust channel. Combined with the adhesive of high-molecular-weight acrylate copolymer, it enhances adhesion and cohesion, ensuring that the tape has sufficient bonding performance and heat dissipation effect under extremely thin conditions.

Benefits of technology

It realizes effective bonding and heat dissipation to electronic components under extremely thin conditions, extends the service life of electronic products and improves performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799180A_ABST
    Figure CN119799180A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of adhesives, and provides a double-sided dotted adhesive tape and a preparation method thereof.The double-sided dotted adhesive tape comprises a base material layer and dotted adhesive layers evenly distributed on the two faces of the base material layer; the dotted adhesive layer is prepared from an adhesive, and the adhesive comprises an acrylate copolymer with the weight-average molecular weight of 2 million to 1 million. The double-sided point-shaped adhesive tape is thin in thickness and has excellent bonding strength, and the design of the point-shaped structure forms an exhaust channel, so that bubble removal and heat dissipation during bonding of bonding parts are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a double-sided dotted adhesive tape and a preparation method thereof. Background Art

[0002] With the rapid development of the consumer electronics industry, the design of electronic devices such as laptops, tablets, and mobile phones is becoming increasingly thinner and lighter, and the matching electronic components are also developing towards thinner and more integrated. Most of the electronic component modules are fixed with double-sided tape to achieve bonding.

[0003] As the functions of electronic components increase and their size decreases, the double-sided tape used to fix electronic components is required to not only have sufficient bonding performance, but also be extremely thin to discharge the heat generated by the electronic components and promote heat dissipation inside the electronics. Traditional double-sided tapes are planar structures. In order to ensure the bonding strength, they need to have a certain thickness, and there is basically no gap between them and the bonded electronic components, resulting in the heat generated by the electronic components not being able to be discharged from the electronic products in time. After a period of use, the electronic products will heat up. Long-term heat accumulation is extremely detrimental to the performance and life of electronic products.

[0004] Based on the above problems, the present invention is proposed. Summary of the invention

[0005] The purpose of the present invention is to solve the problems existing in the prior art and provide a double-sided dotted tape and a preparation method thereof. The double-sided dotted tape is thin and has excellent bonding strength, and the dotted structure design forms an exhaust channel, which helps to dissipate the heat of the bonded parts.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The first aspect of the present invention provides a double-sided dotted tape, which includes a substrate layer and evenly distributed dotted adhesive layers arranged on both sides of the substrate layer; the dotted adhesive layers are prepared by an adhesive, and the adhesive includes an acrylic ester copolymer with a weight-average molecular weight of 700,000 to 1,000,000.

[0008] The present invention adopts a double-sided dotted tape. The design of the dotted structure can not only ensure the bonding effect on the adhered object, but also form an effective exhaust channel when the tape and the adhered object are bonded, which is convenient for heat dissipation of the bonding parts; furthermore, the adhesive of the dotted adhesive layer adopts an acrylic copolymer with a molecular weight of 700,000 to 1,000,000. The molecular weight of the acrylic copolymer is relatively high, which enhances the cohesion of the adhesive and has better stickiness, thereby improving the adhesion of the adhesive.

[0009] In some embodiments, the weight average molecular weight of the acrylate copolymer is 700,000 to 1,000,000, for example, 700,000, 750,000, 800,000, 850,000, 900,000, 950,000, 1,000,000, or any value between the two ends. The inventors of the present invention have found that if the weight average molecular weight of the acrylate copolymer is higher than this range, the pressure-sensitive adhesive has too strong cohesion and poor initial adhesion; if the weight average molecular weight of the acrylate copolymer is lower than this range, the pressure-sensitive adhesive has poor cohesion and reduced adhesion.

[0010] In the present invention, the "cross-section" of the dot-shaped adhesive layer refers to the cross-section of the dot-shaped adhesive layer parallel to the surface of the substrate layer, and can be set to a variety of shapes according to needs, for example, it can be at least one of a polygon (triangle, square, regular pentagon, regular hexagon, rhombus, etc.), a circle, and an ellipse, preferably a circle.

[0011] In some embodiments, the dot diameter of the dot-shaped adhesive layer is 260 to 360 μm, for example, 260 μm, 280 μm, 300 μm, 320 μm, 340 μm, 360 μm or any value between the two end values. The "dot diameter" can be understood as the "diameter of the dot-shaped adhesive layer", that is, the maximum straight-line distance between the two side edges of a dot-shaped adhesive layer in a direction parallel to the substrate layer. Taking the cross-section of the dot-shaped adhesive layer as a circle as an example, the "dot diameter" refers to the diameter of the circle.

[0012] In some embodiments, the dot height of the dot-shaped adhesive layer is 2 to 6 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm or any value between the two end values. The "dot height" can be understood as the vertical distance from the surface of the substrate layer to the top of the dot-shaped adhesive layer; the "dot height" can also be understood as the "thickness of the dot-shaped adhesive layer".

[0013] In some embodiments, the dot spacing of the dot-shaped adhesive layer is 500-600 μm, for example, 500 μm, 520 μm, 540 μm, 560 μm, 580 μm, 600 μm or any value between the two end values. The "dot spacing" can be interpreted as the straight-line distance between the centers of adjacent dot-shaped adhesive layers. For example, if the cross section of the dot-shaped adhesive layer is a circle, the "dot spacing" is the straight-line distance between the centers of two adjacent circles.

[0014] In some embodiments, the thickness of the substrate layer is 1 to 6 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm or any value between the two ends. The substrate layer in the present invention is relatively thin, so that the overall thickness of the tape can be relatively thin, which is convenient for adapting to the application of lightweight electronic products.

[0015] The inventors of the present invention have found that by limiting the dot diameter, dot height and dot spacing of the dot-shaped adhesive layer in the double-sided tape within the above-mentioned range, the bonding strength of the tape can be ensured, and when the double-sided tape is bonded to electronic components, there can be an exhaust channel of suitable size between the dot-shaped adhesive layer and the bonding component surface, thereby facilitating heat dissipation.

[0016] In some embodiments, the acrylate copolymer is copolymerized by acrylate monomers. Based on 100 wt% of the total amount of the acrylate monomers, the acrylate copolymer includes the following components: 75-85 wt% of soft monomers, 10-18 wt% of hard monomers and 2-7 wt% of functional monomers.

[0017] In some embodiments, based on 100 wt% of the total amount of the acrylic ester monomer, the content of the soft monomer is 75-85 wt%, for example, 75 wt%, 76 wt%, 78 wt%, 80 wt%, 82 wt%, 84 wt%, 85 wt% or any value in between.

[0018] In some embodiments, the glass transition temperature (Tg) of the soft monomer is -40 to -20°C; specifically, it can be -40°C, -30°C, -20°C, or any value in between. The Tg value of the soft monomer in the present invention is relatively low, which can ensure that the adhesive has a certain viscosity.

[0019] In some embodiments, the soft monomer includes at least one of isobutyl acrylate (Tg: -26°C) and ethyl acrylate (Tg: -22°C), preferably isobutyl acrylate.

[0020] In some embodiments, the glass transition temperature of the hard monomer is 60 to 120°C; specifically, it can be 60°C, 70°C, 90°C, 100°C, 120°C, or any value between the two end values. The hard monomer Tg value in the present invention is relatively high, which can improve the cohesion and strength of the copolymer; in addition, the introduction of high Tg monomers can also improve the plastic deformation resistance of the point-shaped adhesive layer, avoid collapse and deformation of the point-shaped adhesive layer under the action of external force, and ensure the structural stability and uniform distribution of the point-shaped adhesive layer.

[0021] In some embodiments, the hard monomer includes at least one of methyl methacrylate (Tg: 105° C.), ethyl methacrylate (Tg: 65° C.), and tert-butyl methacrylate (Tg: 118° C.), preferably methyl methacrylate.

[0022] In some embodiments, based on the total amount of the acrylic ester monomer as 100wt%, the content of the hard monomer is 10-18wt%, for example, it can be 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 18wt% or any value in between.

[0023] In some embodiments, the functional monomer is a monomer with a polar functional group, wherein the polar functional group includes a carboxyl group (-COOH), a hydroxyl group (-OH), an amide group (-CONH-), an amino group (-NH 2 ). In the present invention, the functional monomer is a monomer with a polar group, which has a high polarity. These polar groups are cross-linked with the curing agent added subsequently, which can enhance the adhesive force of the adhesive and improve the adhesion strength.

[0024] In some embodiments, the functional monomer includes at least one of acrylic acid, methacrylic acid, monobutyl itaconate, β-acryloxypropionic acid, N-hydroxymethyl methacrylamide, N-(hydroxymethyl) acrylamide, N-hydroxyethyl methacrylamide, and hydroxypropyl amino acrylate.

[0025] In some embodiments, the content of the functional monomer is 2-7wt% based on the total amount of the acrylic ester monomer as 100wt%, for example, it can be 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt% or any value between the two end values. If the content of the functional monomer is too little, the cohesion of the adhesive is poor, the bonding performance is poor, and the adhesion on the substrate layer is poor; if the content of the functional monomer is too much, the intermolecular force is too strong, gel is easily generated, the stability of the acrylic ester copolymer is poor, resulting in poor dispersion effect, which is not conducive to the coating and transfer of the adhesive on the gravure roller, and too much functional monomer will lead to excessive cross-linking, causing the adhesive to lose pressure sensitivity.

[0026] In some embodiments, the acrylic ester copolymer further comprises an organic solvent during the copolymerization process, and the amount of the organic solvent added is 150 to 230 parts by weight relative to 100 parts by weight of the total amount of acrylic ester monomers, for example, 150 parts by weight, 160 parts by weight, 170 parts by weight, 180 parts by weight, 190 parts by weight, 200 parts by weight, 210 parts by weight, 220 parts by weight, 230 parts by weight, or any value between the two end values. In the present invention, the type of organic solvent is not specifically limited, and the types of conventional organic solvents in the art are all within the protection scope of the present invention, for example, it can include one or more of ethyl acetate, butanone, n-hexane, and n-heptane.

[0027] In some embodiments, the acrylic ester copolymer further includes an initiator during the copolymerization process. Relative to 100 parts by weight of the total amount of acrylic ester monomers, the added amount of the initiator is 0.1 to 0.3 parts by weight, for example, 0.1 parts by weight, 0.15 parts by weight, 0.2 parts by weight, 0.25 parts by weight, 0.3 parts by weight or any value in between.

[0028] In some embodiments, the initiator includes an azo initiator, for example, one or more of azobisisobutyronitrile, azobisisoheptanenitrile, azobisisovaleronitrile, and dimethyl azobisisobutyrate.

[0029] The copolymerization method of the acrylic ester copolymer of the present invention can adopt a conventional solution polymerization method, for example, the acrylic ester copolymer is obtained by polymerization reaction of measured weight parts of soft monomer, hard monomer, functional monomer, initiator and organic solvent.

[0030] During the polymerization process, nitrogen can be introduced to remove oxygen, and the polymerization can be carried out under sealed conditions. The polymerization temperature can be set to 50-70°C, specifically 50°C, 60°C, 70°C or any value between the two end values, and the polymerization time can be set to 16±4h.

[0031] The weight average molecular weight of the acrylic acid ester copolymer after polymerization is 700,000 to 1,000,000.

[0032] In some embodiments, the adhesive layer of the present invention further includes a curing agent, and the content of the curing agent is 0.1 to 0.5 parts by weight relative to 100 parts by weight of the acrylate copolymer; for example, it can be 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight, 0.5 parts by weight, or any value in between.

[0033] In some embodiments, the curing agent includes a metal titanium salt curing agent. The metal titanium salt curing agent has a fast reaction speed and can quickly react with the copolymer in the adhesive during the drying stage of the adhesive to form a stable ionic bond, thereby avoiding the collapse of the point-shaped adhesive layer caused by long-term curing. At the same time, the metal titanium salt curing agent has a strong and stable ion complexing ability, which can further improve the plastic deformation resistance of the point-shaped adhesive layer in the protective film product and maintain the structural stability of the point-shaped adhesive layer.

[0034] In some embodiments, the metal titanium salt curing agent includes diisopropyl di(acetylacetonate). In some embodiments, a mixture of diisopropyl di(acetylacetonate) titanate and an organic solvent may be used, and the organic solvent may be acetylacetone; preferably, the mass ratio of the diisopropyl di(acetylacetonate) titanate to the acetylacetone is 1:(1.5-2.5), for example, it may be 1:1.5, 1:1.8, 1:2, 1:2.3, 1:2.5 or any value between the two end values. Acetylacetone is used as a solvent to dissolve diisopropyl di(acetylacetonate) titanate before participating in the curing of the adhesive, which facilitates the uniform distribution of the curing agent and has a better curing effect on the adhesive.

[0035] In some embodiments, the adhesive layer of the present invention further includes a tackifying resin, and the content of the tackifying resin is 5 to 15 parts by weight relative to 100 parts by weight of the acrylate copolymer, for example, 5 parts by weight, 7 parts by weight, 9 parts by weight, 11 parts by weight, 13 parts by weight, 15 parts by weight, or any value between the two end values. In the present invention, a tackifying resin is further added to the adhesive, and the tackifying resin can improve the bonding performance of the adhesive. If too much tackifying resin is added, the pressure sensitivity of the adhesive will be weakened, affecting the bonding performance of the double-sided tape; if too little tackifying resin is added, the peeling force will be less improved, resulting in insufficient bonding performance of the double-sided tape.

[0036] In some embodiments, the softening point of the tackifying resin is not less than 110° C. The tackifying resin used in the present invention has a high softening point, which can prevent the tackifying resin from softening during the molding and subsequent use of the double-sided dot tape, causing the double-sided dot tape structure to deform and affect its exhaust and heat dissipation.

[0037] In some embodiments, the tackifying resin is selected from at least one of terpene phenolic resin and rosin resin. The tackifying resin can be a conventional commercial product, specifically including at least one of TP2040, TP7042, 803L, KB120, and NH3010.

[0038] In some embodiments, the adhesive layer of the present invention further includes a dilution solvent during the preparation process. Relative to 100 parts by weight of the acrylate copolymer, the content of the dilution solvent is 150 to 200 parts by weight, for example, 150 parts by weight, 160 parts by weight, 170 parts by weight, 180 parts by weight, 190 parts by weight, 200 parts by weight or any value in between.

[0039] In some embodiments, the dilution solvent includes at least one of ethyl acetate, methyl acetate, butanone, and n-hexane.

[0040] The present invention adopts a volatile solvent that can evaporate quickly, thereby reducing the leveling phenomenon during coating and drying of the dot-shaped adhesive layer and ensuring the molding integrity of the dot-shaped adhesive tape.

[0041] In the present invention, the material of the substrate layer is not specifically limited, and materials commonly used in the art may be selected. For example, the substrate layer may be a polyethylene terephthalate (PET) film or a polyimide (PI) film.

[0042] In some embodiments, the surface of the dot-shaped adhesive layer may be covered with a release film, which is removed during actual use without affecting the thickness of the double-sided tape during actual pasting. The release film may be made of conventional materials, such as PET release film, PE release film, OPP release film, etc. There is no particular limitation on the thickness of the release film, and generally different thicknesses may be used according to actual winding or cost requirements.

[0043] The second aspect of the present invention also provides a method for preparing the double-sided dotted tape described in the first aspect of the present invention, comprising the following steps: placing measured weight portions of an acrylate copolymer, a diluent solvent, a tackifying resin and a curing agent in a stirring barrel and stirring them evenly, and then standing and defoaming to obtain the adhesive to be coated; using a gravure roller to evenly coat the adhesive on the release surface of a release film, and after drying and curing, laminating the substrate layer on the surface of the formed dotted adhesive layer; then using a gravure roller to evenly coat the adhesive on the release surface of another release film, and after drying and curing, laminating the other side of the substrate layer on the surface of the formed adhesive layer, thereby obtaining the double-sided dotted tape.

[0044] The orthographic projection shape of the concave surface of the gravure roller is circular. In order to obtain a dot-shaped adhesive layer that meets the product size, the dot diameter of the gravure roller is 360-460 μm, the concave depth is 20-60 μm, and the dot spacing is 500-600 μm. The dot diameter of the gravure roller can be 360μm, 370μm, 400μm, 420μm, 460μm or any value between the two end values, and the understanding of the dot diameter of the gravure roller is consistent with the understanding of the dot diameter of the dot-shaped adhesive layer, that is, the diameter of the circular concave; the concave depth of the gravure roller can be 20μm, 30μm, 40μm, 50μm, 60μm or any value between the two end values, and the concave depth of the gravure roller is the vertical depth of the concave; the dot spacing of the gravure roller can be 500μm, 520μm, 550μm, 570μm, 600μm or any value between the two end values, and the dot spacing of the gravure roller is consistent with the dot spacing of the dot-shaped adhesive layer, that is, the straight-line distance between the centers of two adjacent concave circles. The double-sided dotted tape prepared by the inventor of the present invention using the gravure roller of the above size has a dotted adhesive layer of suitable size, and the dotted structure of the dotted adhesive layer can not only ensure effective bonding to electronic components, but also form an effective exhaust channel to facilitate heat dissipation of electronic components.

[0045] In some embodiments, the coating viscosity of the adhesive is 500 to 1,500 cPs (25° C.), for example, 500 cPs, 600 cPs, 800 cPs, 1,000 cPs, 1,200 cPs, 1,400 cPs, 1,500 cPs, or any value between the two end values. Controlling the coating viscosity of the adhesive within the above range can make the adhesive have better coating transfer performance. During the tape coating and drying preparation process, the adhesive can be evenly coated on the surface of the substrate to form a dot-shaped adhesive layer with uniform thickness and regular shape, and the structure of the dot-shaped adhesive layer has less collapse and deformation.

[0046] The present invention adopts the above technical solution to achieve the following beneficial effects:

[0047] (1) The double-sided dotted tape provided by the present invention has a stable dotted structure, the tape is thin, the collapse and deformation are small, the dotted structure is evenly distributed, and an effective exhaust channel can be formed, which is helpful for heat dissipation in electronic products;

[0048] (2) The double-sided dotted tape provided by the present invention has excellent adhesion and can effectively bond electronic components. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 This is a 3D microscope magnified image of the dot-shaped adhesive layer prepared in Example 1 of the present invention;

[0050] Figure 2 This is a 3D microscope magnified image of the dot-shaped adhesive layer prepared in Example 5c of the present invention;

[0051] Figure 3 This is a 3D microscope magnified image of the dot-shaped adhesive layer prepared in Example 5d of the present invention;

[0052] Figure 4 This is a 3D microscope magnified image of the dot-shaped adhesive layer prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0053] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0054] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.

[0055] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0056] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources. 1 part by weight in the following examples can be represented by 1 g.

[0057] The present invention is described in detail below in conjunction with specific examples, which are used to understand but not to limit the present invention. The test method for the weight average molecular weight of the acrylic ester copolymer in the following examples of the present invention is tested using the national standard GB / T 21863-2008 "Gel Permeation Chromatography (GPC) Using Tetrahydrofuran as Eluent".

[0058] Example 1

[0059] 1. Preparation of Acrylate Copolymer

[0060] Acrylate copolymer raw material composition:

[0061] Isobutyl acrylate, 80 g;

[0062] Methyl methacrylate, 18 g;

[0063] Hydroxypropyl carbamate acrylate, 2 g;

[0064] Azobisisobutyronitrile, 0.1 g;

[0065] Ethyl acetate, 230 g.

[0066] The above raw materials were mixed and subjected to polymerization reaction to obtain an acrylic ester copolymer with a weight average molecular weight of 840,000.

[0067] 2. Preparation of double-sided dot tape

[0068] Adhesive raw materials composition:

[0069] 100 g of the acrylic acid ester copolymer prepared above;

[0070] The tackifying resin is TP7042 (softening point (ring and ball method) is 148° C.) produced by Kraton Polymers USA LLC, 10 g;

[0071] Curing agent: a mixture of diisopropyl di(acetylacetonate)titanate and acetylacetone in a weight ratio of 1:2, 0.1 g;

[0072] Ethyl acetate, 120g; n-hexane, 30g.

[0073] The above raw materials were stirred and mixed evenly, and after standing and defoaming, an adhesive with a viscosity of 1,000 cPs to be coated was obtained. The adhesive was evenly coated on the release surface of a 50 μm PET release film using a gravure roller (dot diameter 430 μm, concave depth 40 μm, dot spacing 560 μm), and baked in an oven at 100°C for 3 minutes to obtain a dot-shaped adhesive layer, which was bonded to one side of a 2 μm PET substrate; then the adhesive was evenly coated on the release surface of another 50 μm PET release film using a gravure roller of the same specification, and baked in an oven at 100°C for 3 minutes to obtain another dot-shaped adhesive layer, which was bonded to the other side of the above PET substrate to obtain the double-sided dot-shaped tape.

[0074] Example 2

[0075] This example is carried out with reference to Example 1, and its preparation method is the same as that of Example 1, except that the raw material composition of the acrylic ester copolymer and the adhesive is different, and the size of the coating gravure roller is different, and the specific differences are as follows:

[0076] 1. Raw material composition of acrylic copolymer:

[0077] Isobutyl acrylate, 75 g;

[0078] Methyl methacrylate, 18 g;

[0079] β-Carboxyethyl acrylate, 7 g;

[0080] Azobisisobutyronitrile, 0.1 g;

[0081] Ethyl acetate, 150 g.

[0082] The weight average molecular weight of the obtained acrylic acid ester copolymer was 950,000.

[0083] 2. Adhesive raw material composition:

[0084] 100 g of the acrylic acid ester copolymer prepared above;

[0085] TP7042, 15g;

[0086] Curing agent: a mixture of diisopropyl di(acetylacetonate)titanate and acetylacetone in a weight ratio of 1:2, 0.5 g;

[0087] Ethyl acetate, 150g; n-hexane, 50g.

[0088] The dimensions of the coating gravure roller were: dot diameter 360 μm, concave depth 20 μm, and dot spacing 500 μm.

[0089] Example 3

[0090] This example is carried out with reference to Example 1, and its preparation method is the same as that of Example 1, except that the raw material composition of the acrylic ester copolymer and the adhesive is different, and the size of the coating gravure roller is different, and the specific differences are as follows:

[0091] 1. Raw material composition of acrylic copolymer:

[0092] Isobutyl acrylate, 85 g;

[0093] Methyl methacrylate, 10 g;

[0094] Methacrylic acid, 5 g;

[0095] Azobisisobutyronitrile, 0.3 g;

[0096] Ethyl acetate, 150 g.

[0097] The weight average molecular weight of the obtained acrylic acid ester copolymer was 720,000.

[0098] 2. Adhesive raw material composition:

[0099] 100 g of the acrylic acid ester copolymer prepared above;

[0100] TP7042, 5g;

[0101] Curing agent: a mixture of diisopropyl di(acetylacetonate)titanate and acetylacetone in a weight ratio of 1:2, 0.1 g;

[0102] Ethyl acetate, 120 g; Butanone, 30 g.

[0103] The dimensions of the coating gravure roller are: dot diameter 460 μm, concave depth 60 μm, and dot spacing 600 μm.

[0104] Example 4 Group

[0105] This example group was prepared with reference to Example 1, and its raw material composition and preparation method were the same as those of Example 1, except that the type of tackifying resin of the adhesive was different, and the specific differences are as follows:

[0106] Example 4a: The tackifying resin is NH3000 produced by Harima Chemicals Co., Ltd. of Japan, and has a softening point (ring and ball method) of 140-150°C;

[0107] Example 4b: The tackifying resin is KB120 produced by Guangdong Kemao Forestry Group Co., Ltd., and the softening point (ring and ball method) is 115-125°C;

[0108] Example 4c: The tackifying resin is TP2040 produced by Kraton Polymers USA LLC, and has a softening point (ring and ball method) of 119°C;

[0109] Example 4d: The tackifying resin is NH2000 produced by Harima Chemicals Co., Ltd. of Japan, and has a softening point (ring and ball method) of 96-102°C.

[0110] Example 5 Group

[0111] This example group was prepared with reference to Example 1, and its raw material composition and preparation method were the same as those of Example 1, except that the coating viscosity of the adhesive was adjusted by adjusting the amount of diluent used for the adhesive, and the specific differences are as follows:

[0112] Example 5a: 250 g ethyl acetate, 40 g n-hexane, the coating viscosity of the adhesive is 500 cPs;

[0113] Example 5b: 80 g ethyl acetate, 10 g n-hexane, the coating viscosity of the adhesive is 1,500 cPs;

[0114] Example 5c: 50 g ethyl acetate, 10 g n-hexane, the coating viscosity of the adhesive is 1,700 cPs;

[0115] Example 5d: 310 g ethyl acetate, 50 g n-hexane, the coating viscosity of the adhesive is 400 cPs.

[0116] Comparative Example 1

[0117] This comparative example was prepared with reference to Example 1, and its preparation method was the same as that of Example 1, except that an equal amount of epoxy curing agent (TETRAD-C produced by Mitsubishi Gas Chemical Co., Ltd. of Japan) was used instead of the adhesive.

[0118] Comparative Example 2

[0119] This comparative example was prepared with reference to Example 1, and its raw material composition and preparation method were the same as those of Example 1, except that the size of the gravure roller was different, and the specific differences are as follows:

[0120] Comparative Example 2a: The dot diameter of the gravure roller is 330 μm, the concave depth is 15 μm, and the dot spacing is 450 μm;

[0121] Comparative Example 2b: The dot diameter of the gravure roller is 480 μm, the concave depth is 80 μm, and the dot spacing is 650 μm.

[0122] Comparative Example 3

[0123] This group of comparative examples was prepared with reference to Example 1. The raw material composition and preparation method were the same as those of Example 1. The difference was that the molecular weight of the acrylate copolymer was controlled by adjusting the amount of initiator. In order to maintain the coating viscosity, the amount of the diluent in the adhesive was also adjusted. The specific differences are as follows:

[0124] Comparative Example 3a: 0.8 g of azobisisobutyronitrile, the molecular weight of the obtained acrylic ester copolymer is 580,000, and the diluent in the adhesive is 50 g of ethyl acetate and 10 g of n-hexane;

[0125] Comparative Example 3b: 0.05 g of azobisisobutyronitrile, the molecular weight of the obtained acrylic ester copolymer is 1.12 million, and the diluent in the adhesive is 220 g of ethyl acetate and 50 g of n-hexane.

[0126] Test items and test methods:

[0127] The adhesive tapes prepared in the above embodiments and comparative examples were used for the following performance tests, and the test results are recorded in Table 1.

[0128] 1. 180° peel force test

[0129] The 180° peeling force test is carried out in accordance with the national standard GB / T 2792-2014 "Test method for peeling strength of adhesive tape". The test plate is a mirror steel plate, and the mirror steel plate is wiped three times with ethanol before the test. Take a 300mm×24mm double-sided dot tape sample, peel off the release film on one side of the double-sided dot tape, stick the dot adhesive layer of the double-sided dot tape on the wiped mirror steel plate, roll it twice with a 2kg roller, place the test sample in a controlled environment (23℃±2℃ / 50%±5%RH) for 20 minutes, and then test its 180° peeling force. The peeling speed is 300mm / min. Based on the application scenario of the double-sided dot tape described in the present invention, its 180° steel plate peeling force is not less than 150gf / 24mm, preferably not less than 200gf / 24mm, to ensure that the double-sided dot tape has good adhesion.

[0130] 2. Dimensional test of dot adhesive layer

[0131] Under a 3D microscope (100 times), 10 dot-shaped adhesive layers were randomly selected as test objects, and their diameters, dot spacings and dot heights were measured in a controlled environment (23±2°C / 50±5%RH). The average values ​​were recorded as the initial dot diameter, dot spacing and dot height of the dot-shaped adhesive layer. The results are recorded in Table 1.

[0132] In order to further test the high temperature resistance of the double-sided dotted tape of the present invention, the double-sided dotted tape was placed in a controlled environment (23±2℃ / 50±5%RH) for 3 days, then placed in a 50℃ oven for 72h, and then taken out and placed in a controlled environment (23±2℃ / 50±5%RH) for 16h. The dot diameter and dot height were measured using a 3D microscope, and the testing method was the same as above.

[0133] 3. Appearance judgment: Take a 30mm×100mm double-sided dot tape sample, peel off the release film, and observe the appearance of the dot adhesive layer under a 3D microscope (100 times). If the dots are uniform and independently distributed, it is recorded as OK; otherwise, the abnormal appearance is recorded.

[0134] Table 1

[0135]

[0136]

[0137] Note: The mark “ / ” in the above dimension measurement of the dot-shaped adhesive layer indicates that the product appearance is poor and its dimensions cannot be measured correctly.

[0138] According to the above test results, the dot-shaped double-sided tape prepared by the present invention has a thin adhesive layer, a 180° peeling force on a steel plate of not less than 200gf / 24mm, good adhesion, and a uniform and independent distribution of the dot-shaped adhesive layer. Figure 1 As shown, an effective exhaust and heat dissipation channel can be formed. At the same time, after long-term high-temperature (50°C) pasting, the height of the dot-shaped adhesive layer of the double-sided tape changes little, and although the dot diameter changes to a certain extent, the tape can still have an exhaust channel suitable for product heat dissipation, and the overall deformation is small.

[0139] It can be seen from the test results of Example 4 that by using a resin with a softening point above 110°C, a tape with better performance can be obtained; if the softening point is lower than 110°C, the point diameter formed is relatively large, and point overlap occurs after long-term high-temperature bonding, and the original exhaust and heat dissipation channels cannot be retained.

[0140] The test results of Example 5 show that if the coating viscosity of the adhesive is too high and the fluidity is poor, it will lead to poor coating transfer and form coating flying silk, such as Figure 2 As shown in the figure, the shape of the dot-shaped adhesive layer is deformed and uneven; if the coating viscosity of the adhesive is low and the fluidity is too good, the adhesive will flow out from the holes before it is completely transferred to the release film, resulting in poor coating and molding, such as Figure 3 As shown, the low coating viscosity of the adhesive will also lead to a decrease in the effective ingredients of the adhesive, a thinner thickness of the adhesive, and a lower peel force.

[0141] The test results of Comparative Example 1 show that if an epoxy curing agent with a slower curing speed is used in the present invention, the adhesive will not have enough time to cure, and a stable cross-linked network structure will not be formed between molecules. The intermolecular force is weak, and the adhesive leveling ability is poor, resulting in poor formation of the point-shaped adhesive layer and point overlap. Figure 4 shown.

[0142] It can be seen from the test results of comparative example 2 that if the size of the coating gravure roller used is lower than the specified range of the present invention, the thickness of the formed point-shaped adhesive layer will be thinner, the peeling force will be lower, and it will not be able to effectively fit; if the size of the coating gravure roller used is higher than the specified range of the present invention, the point height of the formed point-shaped adhesive layer will be higher, the adhesive will not be completely transferred from the point holes, and flying wires will occur.

[0143] It can be seen from the test results of the comparative example 3 that when the molecular weight of the acrylic copolymer used in the present invention is low, the single molecule is small, the intermolecular force is small, the internal friction that the molecular movement needs to overcome is small, the flow resistance is small, and the fluidity of the overall adhesive is improved. If the flow is too fast, the adhesive will flow out of the holes before being transferred to the release film, and the adhesive cannot be well formed. If the molecular weight of the acrylic copolymer is high, the larger the single molecule, the easier it is for the molecules to form entanglements and hydrogen bonds, the greater the internal friction that the molecular movement needs to overcome, the flow resistance is too large, and the transfer speed is slow, the overall adhesive fluidity is poor, resulting in coating flying silk, a small coating transfer amount, a thinner dot-shaped adhesive layer formed, and a reduced peel force.

[0144] It should be noted that, in this article, the terms "comprise", "include" or any other variants thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0145] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A double-sided dotted tape, characterized in that: The double-sided dot-shaped adhesive tape comprises a substrate layer and evenly distributed dot-shaped adhesive layers arranged on both sides of the substrate layer; the dot-shaped adhesive layers are prepared from an adhesive, and the adhesive comprises an acrylic ester copolymer with a weight average molecular weight of 700,000 to 1,000,000.

2. The double-sided dotted tape according to claim 1, characterized in that: The cross section of the dot-shaped adhesive layer is circular.

3. The double-sided dotted tape according to claim 1 or 2, characterized in that: The dot diameter of the dot adhesive layer is 260-360 μm, the dot height is 2-6 μm, and the dot spacing is 500-600 μm; And / or, the thickness of the substrate layer is 1 to 6 μm.

4. The double-sided dotted tape according to claim 1, characterized in that: The acrylic ester copolymer is formed by copolymerization of acrylic ester monomers, and includes the following components based on the total amount of the acrylic ester monomers being 100wt%: 75-85wt% of soft monomers, 10-18wt% of hard monomers, and 2-7wt% of functional monomers with polar functional groups; Wherein, the glass transition temperature of the soft monomer is -40 to -20°C; The glass transition temperature of the hard monomer is 60 to 120°C; The polar functional group includes at least one of a carboxyl group, a hydroxyl group, an amide group, and an amino group.

5. The double-sided dotted tape according to claim 4, characterized in that: The soft monomer includes at least one of isobutyl acrylate and ethyl acrylate; And / or, the hard monomer includes at least one of methyl methacrylate, ethyl methacrylate, and tert-butyl methacrylate; And / or, the functional monomer includes at least one of acrylic acid, methacrylic acid, monobutyl itaconate, β-acryloxypropionic acid, N-hydroxymethyl methacrylamide, N-(hydroxymethyl) acrylamide, N-hydroxyethyl methacrylamide, and hydroxypropyl aminomethacrylamide.

6. The double-sided dotted tape according to claim 1, characterized in that: The adhesive further comprises a curing agent and a tackifying resin. With respect to 100 parts by weight of the acrylic ester copolymer, the content of the curing agent is 0.1 to 0.5 parts by weight, and the content of the tackifying resin is 5 to 15 parts by weight.

7. The double-sided dotted tape according to claim 6, characterized in that: The curing agent includes a metal titanium salt curing agent; Preferably, the metal titanium salt curing agent includes diisopropyl di(acetylacetonate)titanate.

8. The double-sided dotted tape according to claim 6, characterized in that: The tackifying resin includes at least one of terpene phenolic resin and rosin resin; Preferably, the softening point of the tackifying resin is not lower than 110°C.

9. A method for preparing the double-sided dotted adhesive tape according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: applying adhesive uniformly to the release surface of a release film by using a gravure roller, and after drying and curing, laminating the substrate layer on the surface of the formed dot-shaped adhesive layer; and then applying adhesive uniformly to the release surface of another release film by using a gravure roller, and after drying and curing, laminating the other side of the substrate layer on the surface of the formed dot-shaped adhesive layer, so as to obtain a double-sided dot-shaped adhesive tape.

10. The preparation method according to claim 9, characterized in that: The adhesive has a coating viscosity of 500 to 1,500 cPs.